Environmental Literacy of Students in Al-Rifa'ie Modern Islamic Boarding School, Malang Regency-Indonesia Based on Gender Differences and Parents' Occupation - Nina Dwi Mardiani; Husamah Husamah; Diani Fatmawati; Fuad Jaya Miharja*; Ahmad Fauzi (Jurnal Pendidikan Sains Indonesia, 2021)
Many students in Indonesia are not responsive about the environmental problems around them. This study aimed to (1) analyze environmental literacy differences between male and female students, (2) analyze environmental literacy differences based on gender and parental occupations, and (3) analyze the influence of the interaction between gender and the parents’ occupations. This study used a quantitative approach. This study consisted of 70 students in 11th grade as a subjects. The subjects were determined randomly in three majors, i.e. multimedia, nursing, and pharmacy. Students' environmental literacy was measured using the MSELS instrument developed by McBeth, 2011. The results study showed that no significant difference in knowledge and cognitive skills between male and female students, but there were significant differences in attitudes and behavior. Moreover, there was no significant difference in knowledge, attitudes, and cognitive skills between students whose parents work. However, there were significant differences in behavior between students whose parents' jobs were different. There is a significant relationship between male students in the aspects of knowledge, attitudes, behavior, and cognitive skills, but not significantly related to female students' behavior. There was no significant interaction between male and female students and their parents' different environmental literacy occupations.